Toxics - MDPI (MDPI, 2026)
Toxics is an international, peer-reviewed, open access journal on all aspects of the toxic chemicals and materials, published monthly online by MDPI.
Keywords: Toxicología ambiental; Revistas depredadoras; Predatory journals